CIAM 8. The Heart of the City as the symbolical resilience of the city - Zuccaro Marchi, Leonardo (International Planning History Society Proceedings, 2016)
The “Heart of the City”, title of the 8th CIAM (Congrès Internationaux d'Architecture Moderne), held in 1951, is a contradictory and pervasive figure of speech which has marked a thinking and urban transition after the 2nd World War and still affects our contemporary urban and social condition. In 1951, two opposite urban conditions are considered by Sert, President of CIAM, as main issues which the Heart discourse should face: from the disappearance of city centres because of the destruction of the War to the negation of the urban centrality because of urban sprawl and the infinite constant enlargement of city boundaries. But the Heart itself also represents two different figures of speeches, the symbol and the metaphor: from one side it becomes a humanist symbol “which springs directly to the senses without explanation”, in opposition to the “mechanized killing”, to the “tyranny of mechanical tools” as stressed by Giedion during CIAM 8; from the other side the Heart still keeps its anatomical metaphorical organic meaning translated into a presumed right physical form and dimension of the city. These oppositions - from annulled bombed centers to infinite urban structures, from metaphor to symbol, from pro-urban to proto-urban Idea are the main causes of the complexity and of the stratification of several different layers of significances of the Heart of the City, since CIAM 8 until the present. Starting from CIAM 8, the paper investigates this Post-war urban tension, which lies at the crossroads of intellectual-theoretical and architectural-design worlds. On the one hand, there is the resilience of the decontextualized social-spatial tabula rasa created by the dangerous mechanical progress which led to the blood and horror of the War. While on the other, the resilience of embracing, stemming, and compressing the Galileo scandal, “the constitution of an infinite, and infinitely open space” (Foucault, 1967) which was, for the first time, mirrored in the urban sprawl. The aim of this paper is to focus on the complexity and the difficulty of interpreting the Heart of the City, from the tangible Janus-faced binomial reconstruction-recentralization of the urban Core, to the symbolical abstract resilience of the Heart as a constituent element at the foundation of the urban structure and anticipator of an anthropological idea of Habitat as an integrating part of the human settlement. From this analysis, the paper states that the Heart does not only concern the Post War reconstruction of the cities as has been generally thought. On the contrary, the Heart of the City is still a valid issue in our contemporary urban condition and it deals with the progressive, contemporary topic of a correct synergy between social and physical space, between the private and public sphere.